Strategi Manajemen Modal Kerja Internasional pada Perusahaan Rantai Pasok Global di Era Disrupsi Digital : Analisis Library Research - Wahyu Wahid; Tafana Ariani Harahap; Nurlela; Khaidar Rahmaini Jamila (MERDEKA : Jurnal Ilmiah Multidisiplin, 2026)
The increasing complexity of global supply chains and the rapid acceleration of digital transformation have created new challenges for multinational companies, particularly in managing international working capital. Digital disruption has not only reshaped cross-border business operations and transactions but has also intensified liquidity risks, cash flow imbalances, and short-term financial uncertainty. These conditions require global supply chain companies to develop adaptive, integrated, and technology-driven working capital management strategies. This study aims to examine international working capital management strategies implemented by global supply chain companies in the era of digital disruption and to identify their implications for corporate stability and sustainability. The research employs a qualitative method using a library research approach. Data were collected through a systematic review of academic books, scholarly journal articles, and official reports from international institutions relevant to the research topic. Data analysis was conducted using content analysis techniques to identify key patterns, concepts, and findings within the literature. The results reveal four main findings: the importance of efficient management of cash, receivables, and inventories across countries; the strategic role of digitalization and data-driven approaches in enhancing transparency and decision-making speed; the significance of financial coordination among global supply chain actors; and the necessity of financial risk mitigation strategies amid global uncertainty.